Indigenous nationals, Canadian citizens: from first contact to Canada 150 and beyond - Courchene, Thomas J. (Institute of Intergovernmental Relations, School of Policy Studies, Queen's University, 2018)
Indigenous Nationals/Canadian Citizens begins with a detailed policy history from first contact to the Sesquicentennial with major emphasis on the evolution of Canadian policy initiatives relating to Indigenous peoples. This is followed by a focus on the